2012
DOI: 10.3389/fnins.2012.00044
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Activation of Protein Kinase A Regulates GABAA Receptor Subunit Expression in the Cerebral Cortex and Contributes to Ethanol-Induced Hypnosis

Abstract: Protein kinases are implicated in neuronal cell functions such as modulation of ion channel function, trafficking, and synaptic excitability. Both protein kinase C (PKC) and A (PKA) are involved in regulation of γ-aminobutyric acid type A (GABAA) receptors through phosphorylation. However, the role of PKA in regulating GABAA receptors (GABAA-R) following acute ethanol exposure is not known. The present study investigated the role of PKA in the effects of ethanol on GABAA-R α1 subunit expression in rat cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 54 publications
7
37
0
Order By: Relevance
“…This change in surface expression was postulated to be due to an increase in synaptic a4bg2 receptors because GABA A d subunit surface expression remained unchanged. Interestingly, the trafficking changes mediated by PKC are mitigated by concurrent activation of PKA by ethanol both in vivo and in vitro (Kumar et al, 2012;Carlson et al, 2013). Furthermore, we found that mice lacking the PKA regulatory subunit RIIb gene have enhanced vulnerability to reductions in extrasynaptic GABA A a4 subunit trafficking after acute ethanol challenge (Carlson et al, 2014).…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…This change in surface expression was postulated to be due to an increase in synaptic a4bg2 receptors because GABA A d subunit surface expression remained unchanged. Interestingly, the trafficking changes mediated by PKC are mitigated by concurrent activation of PKA by ethanol both in vivo and in vitro (Kumar et al, 2012;Carlson et al, 2013). Furthermore, we found that mice lacking the PKA regulatory subunit RIIb gene have enhanced vulnerability to reductions in extrasynaptic GABA A a4 subunit trafficking after acute ethanol challenge (Carlson et al, 2014).…”
Section: Introductionmentioning
confidence: 60%
“…Recent studies by our laboratory have elucidated that protein kinases play a major role in facilitating the regulation of GABA A receptors after ethanol exposure (Kumar et al, 2010;Werner et al, 2011;Kumar et al, 2012). Ethanol has long been known to activate both protein kinase A (PKA) (Dohrman et al, 1996) and protein kinase C (PKC) (Messing et al, 1991), and kinases are important regulators of the behavioral effects of ethanol (Harris et al, 1995;Hodge et al, 1999;Thiele et al, 2000;Choi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our present results demonstrate modulation of GABA A receptor a1 subunit abundance by PKA in vitro, our previous results suggest the same processes occur in vivo (Kumar et al, 2012). Recently, we found that GABA A a1 levels in rat cerebral cortex were increased following an acute ethanol injection, concurrent with an increase in PKA, whereas PKC was unchanged.…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, PKA has been shown to directly phosphorylate and modulate GABA A receptor activity (Ives et al, 2002;Brandon et al, 2003). Recently, we found that ethanol doseand time-dependently increased PKA membrane levels in rat cerebral cortex, which corresponded to increased GABA A a1 subunit expression (Kumar et al, 2012). The precise physiological consequences of ethanol regulation of GABAergic inhibition via PKA, however, are unclear.…”
Section: Introductionmentioning
confidence: 99%